2018
DOI: 10.1021/acs.iecr.8b02278
|View full text |Cite
|
Sign up to set email alerts
|

Separation Performance in a Novel Coupled Cyclone with Built-in Circulating Granular Bed Filter (C-CGBF)

Abstract: A compact dedust scheme coupling a cyclone with a built-in circulating granular bed filter (C-CGBF) for continuous hot gas cleanup is introduced. The effects of the operation parameters including the inlet dust concentrations, the inlet gas flow rates and the granules circulation fluxes on the separation performance of the C-CGBF are experimentally investigated using the FCC catalyst particles in a cold model setup. Experimental results reveal that stable/ high collection efficiency, generally higher than 98%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…For the best performance, the inlet angle should be kept with 10-15°. In view of the inefficiency on 5-10 μm particles, the literature (Huang et al 2018;Gao et al 2018;Safikhani et al 2016) had made some innovations and developed several new separators. These separators have reasonable pressure drop, and the separation efficiency is greatly improved.…”
Section: Introductionmentioning
confidence: 99%
“…For the best performance, the inlet angle should be kept with 10-15°. In view of the inefficiency on 5-10 μm particles, the literature (Huang et al 2018;Gao et al 2018;Safikhani et al 2016) had made some innovations and developed several new separators. These separators have reasonable pressure drop, and the separation efficiency is greatly improved.…”
Section: Introductionmentioning
confidence: 99%
“…The difference was that the cross-flow GBF was used in their studies. Gao et al conducted detailed experiments to figure out the composition of the pressure drop. You et al reported that the maximum tangential velocity was located at the inlet section, which was around 1.2 times larger than the inlet gas velocity based on the simulation results.…”
Section: Introductionmentioning
confidence: 99%